2022
DOI: 10.1111/sode.12608
|View full text |Cite
|
Sign up to set email alerts
|

Decisions and mechanisms of intergroup bias in children's third‐party punishment

Abstract: Acknowledgements:We thank Irina Aragon, Carolina Garrigue, and Camila Sturla for their help in data collection. We would also like to thank the director and staff of the Instituto Sagrada Familia and the Science Cultural Center for providing the facilities for this study. Ethics approval:All children included in this study provided a verbally informed assent, and a parent or guardian gave written informed consent on behalf of the child enrolled in the studies. These written informed consents follow the norms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In other words, adolescents, like children and adults, care about and defend their group membership and are willing to forgive in-group violators. However, Gonzalez-Gadea et al (2022) found that children aged 6 to 9 exhibited an ingroup policing bias but not an ingroup favoritism bias. One potential explanation for the difference is the cost of punishment.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In other words, adolescents, like children and adults, care about and defend their group membership and are willing to forgive in-group violators. However, Gonzalez-Gadea et al (2022) found that children aged 6 to 9 exhibited an ingroup policing bias but not an ingroup favoritism bias. One potential explanation for the difference is the cost of punishment.…”
Section: Discussionmentioning
confidence: 84%
“…Like previous research, this study is subject to several limitations. Initially, the third-party punishment game used in our study involves costless self-reported punishment, which might be different from incentivized punishment ( Gummerum et al, 2016 , 2020 , 2022 ; Gonzalez-Gadea et al, 2022 ). Future studies should explore how TPP with real monetary incentives are affected by group membership.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation